2018
DOI: 10.5606/archrheumatol.2018.6332
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Smoking and Structural Damage, Autoimmune Antibodies, and Disability in Rheumatoid Arthritis Patients

Abstract: Although smoking is known as a poor prognostic factor in RA, there was no correlation between disease activity and smoking in our study. However, less radiographic damage was found in never smokers. Smoking does not appear to correlate with RA disease activity but it may be effective in the long-term joint damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…It has been reported that males are more susceptible to CS than females with respect to RA development [52]. CS can even affect treatment response to disease-modifying anti-rheumatic drugs (DMARDs) [53] and thus can be a risk of future joint destruction [54][55][56].…”
Section: Cigarette Smoking As the Most Robust Environmental Risk Of Ramentioning
confidence: 99%
“…It has been reported that males are more susceptible to CS than females with respect to RA development [52]. CS can even affect treatment response to disease-modifying anti-rheumatic drugs (DMARDs) [53] and thus can be a risk of future joint destruction [54][55][56].…”
Section: Cigarette Smoking As the Most Robust Environmental Risk Of Ramentioning
confidence: 99%
“…GRB has received research grants from AbbVie, Pfizer, Roche, and UCB, and has received consulting fees or other remuneration (payment) or participated in speakers' bureaus from/for AbbVie, Eli Lilly, Merck Sharp & Dohme, Pfizer, Roche, Sanofi Genzyme, and UCB. 4 Seoul National University College of Medicine, Seoul, South Korea. 5 Sanofi, Bridgewater, NJ, USA.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) affects nearly 20 million people worldwide [1] and is associated with substantial morbidity and disability [2]. The consequences of RA disease progression on patient health may be influenced by multiple genetic and environmental factors [3], and specific subpopulations of patients with RA can be characterized on the basis of differences in demographic variables, clinical features, and biomarkers, some of which have been shown to be associated with disease outcomes and therapeutic responses [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…En algunos estudios se ha encontrado que ciertos componentes del humo del cigarro como la nicotina, hidrocarburos y el monóxido de carbono, elevan la reacción inmunológica de las personas con AR 21 . Así mismo, se asocia el tiempo-exposición al tabaco con el riesgo de padecer la enfermedad 22 , así como la existencia de una relación significativa entre el daño articular progresivo y niveles altos de factor reumatoide, con el hábito de fumar por largo tiempo 23 .…”
Section: Introductionunclassified